Improving Teacher Digital Literacy through Wordwall Training in the Tegalwaru District Teacher Working Group Forum Community - Yulian Dinihari; Endang Sulistyaniningsih; Laksita Nirmala Putri; Yulistiana; Marisha Ayuardini (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe how teachers' digital literacy improves through training in using Wordwall as an interactive learning medium. The study was conducted in April–May 2025 and involved 20 elementary school teachers participating in the Teacher Working Group Forum Community in Tegalwaru District, Karawang Regency. The approach used was a descriptive, qualitative approach, with data collection through in-depth interviews, observation of training activities, and documentation of teachers' digital work. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion, and triangulation was carried out to ensure the validity of the results. The results showed that Wordwall training improved four aspects of teachers' digital literacy: technical, pedagogical, social-collaborative, and digital ethics. Teachers became more reflective and creative in designing technology-based learning, and showed increased adaptability to digital developments. Despite obstacles such as limited infrastructure, differences in digital skills, and limited time, teachers still showed resilience. They took the initiative to build collaborative networks through the Teacher Working Group Forum community.